Factors Affecting the Academic Performance of BSHM Working Students in Bestlink College of the Philippines Novaliches, Quezon City S.Y. 2022-2023: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today's generation, academic performance is very important, especially for workingstudents who work just to continue their studies because good academics are a big help forstudents who are more likely to have better employment benefits, higher incomes, and greaterlevels of self-confidence and self-esteem. Students struggle to balance working, studying, andfamily obligations without having a negative impact on their academic performance. Thisresearch aims to encourage working students to pursue and complete a college degree to becompetitive in the future.The study utilized a descriptive research method, which was distributed to a hundred (100)working students, 25 representatives from each of all levels, from the 1st to the 4th year in theBestlink College of the Philippines Novaliches, Quezon City. The researchers used simplesampling techniques in disseminating questionnaires to the respondents. This study is limitedonly to students who are currently enrolled and who are also working at Bestlink College of thePhilippines Novaliches, Quezon City. Only those BSHM working students are allowed toparticipate in the research.There should be a consideration when it comes to the age of the students who want to work;there are students who want to work, but some of them are not qualified because of agequalification. The school must have at least a job fair inside the campus for those who want towork while studying, and, in that way, they can help the students get jobs. Apply to thescholarships offered by the government and other organizations that are willing to help thosewho are deserving of their support.
Keywords: Hospitality Management